PEMBUATAN AKTA PERDAMAIAN DALAM PENYELESAIAN SENGKETA TANAH ULAYAT MELALUI NOTARIS DIKABUPATEN AGAM - Rasyad, Muhamad (Soumatera Law Review, 2019)
Ulayat Right is the highest right onto land owned by a legal alliance (county, tribe) to guarantee the utilization of the land. The Ulayat Right is absolutely owned by its legal alliance (county, tribe) in which the citizens (law alliance) have the right to control the land. The implementation of the land control is governed by the leader of the alliance, including the chief of the tribe and the head of the village or county.  Other regulation on the land is ruled in PMNA/Ka.BPN No.5, 1999 year, such as Article 2 section (1) regulates the implementation of Ulayat Rights insofar as they are still conducted by the customary law community based on its local customary law. However, in Article 3 there is an exception that the implementation of Ulayat Right cannot be carried out anymore to the areas of land atthe time of its enactment.